Effect of omega-3 fatty acids on appetite, energy and macronutrient intake and body weight in obese adults: a randomized clinical trial - Safaeiyan, Abdolrasoul; Ostadrahimi, Alireza; Sanayei, Mahzad; Rasmi, Yousef; Taraghijou, Parizad (Progress in Nutrition, 2018)
Background: Obesity as an important health problem can be solved by modulating the appetite, somewhat. Polyunsaturated fatty acids (PUFA) can modulate appetite and by the way be helpful in weight loss. Method: We investigated the effect of omega-3 fatty acids on appetite, energy and macronutrient intake and weight in obese adults. 66 participants were randomly allocated in intervention and placebo group, and consumed omega-3 and paraffin soft gels respectively, 1000mg twice a day for four weeks. Results: Repeated measure method analysis did not show any significant change in Visual Analogue Scale for appetite and weight in 2 treatments (P=0.46). Dietary intakes of total fat, PUFA, Monounsaturated fatty acids (MUFA) and cholesterol had a significant decrease in treatment group in comparison with placebo (P< 0.05). Energy and protein intakes changed within two groups significantly (P< 0.05). Conclusion: This study shows that increasing intake of omega-3 fatty acids would be helpful for weight loss in obese adults.